Control of blood pressure in hypertensive children and adolescents assessed by ambulatory blood pressure monitoring - Kevalin Vigraijaroenying; Kwanchai Pirojsakul; Poomiporn Katanyuwong; Kanchana Tangnararatchakit; Pawaree Saisawat; Songkiat Chantarogh; Witchuri Paksi; Uthen Bunmee (BMC, 2024)
Abstract Background There have been few studies evaluating the control of hypertension (HT) in children. This study aimed to assess the control of HT using ambulatory blood pressure monitoring (ABPM) and to compare the parameters between the uncontrolled HT and controlled HT groups. Methods Hypertensive patients aged ≥ 5 years who underwent ABPM to assess the control of HT were enrolled. Demographics, office blood pressure (BP), ABPM, and echocardiographic data were collected. Controlled HT was defined using a BP goal recommended by the 2016 European Society of Hypertension guidelines. Results There were 108 patients (64.8% males) with a mean age of 14.3 years and 51.9% had primary HT. Controlled HT was detected in 41.1% and 33.3% by office BP and ABPM, respectively. Based on ABPM, there was a greater prevalence of controlled HT in the primary HT than the secondary HT group (44.6% vs. 21.2%, P = 0.01). In the primary HT group, BMI z-score at the last follow-up had a significant decrease in the controlled HT than the uncontrolled HT group (-0.39 vs. 0.01, P = 0.032). Primary HT was negatively associated with uncontrolled HT by ABPM. In addition, ABPM showed greater sensitivity (77.8% vs. 55.8%) and negative predictive value (80.9% vs. 70.8%) to predict LVH than those of office BP measurement. Conclusion Only one-third of patients achieved the BP goal by ABPM and most were in the primary HT group. Weight reduction is an important measure of BP control in patients with primary HT to attenuate the risk of LVH.